Hubungan Antara Pencegahan Stunting dan Pemahaman Fiqih Parenting - Ahmad Syaripudin; Kharisma Dea Senja; Nurul Andini; Meilisa Sajdah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Stunting is the impaired growth and development of children due to long-term malnutrition. Stunting can be caused by malnutrition experienced by the mother during pregnancy, or the child during their growth period. Stunting is a condition when children experience physical and cognitive growth delays, which can have a negative impact on their health and future. In the Islamic view, the prevention of stunting is an important task that Muslim societies should take on, in line with Allah's command not to be a weak people. Islam teaches to take good care of children and pay special attention to their growth and development. The relationship between stunting prevention and parenting in Islamic fiqh is an important aspect in ensuring the health and well-being of children, especially in the early years of life. Stunting, defined as a condition of stunted growth and development due to malnutrition, is a globally significant public health problem. Parenting in fiqh based on Islamic principles emphasizes the importance of proper nutrition and care of children to prevent stunting. The type of research used in this journal is quantitative research where this research is based on the philosophy of positivism, which is a philosophical teaching that views reality, symptoms, phenomena as classifiable, relatively fixed, concrete, observable, measurable, and relationships. This research was conducted in Tanjung Seneng sub-district, Kec. South Kotabumi, North Lampung Regency, Lampung, with a population of 85% and a sample size of 70%. Data collection was carried out by filling out the Millennial Parenting Style questionnaire and the Early Detection questionnaire in preventing stunting in toddlers.